Impact of the glottal signal on the prediction of speech - Protić, Danijela D. (Vojnotehnički glasnik / Military Technical Courier, 2014)
In this paper, several linear and nonlinear techniques for speech processing based on AR, ARX, ARMAX, WLS and FNN models are proposed. The impact of the glottal wave to modelling is also shown in details. GD, BPA and LM approximations are used for model training and optimization. A comparative experimental analysis of five considered models is done based on the prediction of a speech signal. The results on training and testing are presented through learning and training errors for all models given.